STUDI KUANTITATIF PERBANDINGAN TINGKAT KEPUASAN PASIEN BPJS DAN NON BPJS TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS - Hidayat, Afif Wahyudi; Kadir, Abd; Saputra, M. Khalid Fredy; Mauludiyah, Zaida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Increasing the effectiveness of health services can only be achieved if the quality of services provided by a health institution is always maintained, maintained, and continuously developed. The purpose of this study was to determine the factors associated with the incidence of anemia in pregnant women. The research design used in this study was cross sectional. The research was conducted at the Setia Janji Health Center. The research was conducted in July 2024. The population was all patients who visited the Setia Janji Health Center. The sample amounted to 83 respondents. The sampling technique used in this study was Accidental sampling. Data analysis was carried out univariate and bivariate. The results showed that all dimensions of health service quality have a relationship with patient satisfaction. It is recommended to the Puskesmas to be able to improve the quality of health services consisting of administrative officers, health worker services, and pharmacy services in order to provide friendly and attentive service to patients and provide clear information to patients.Keywords: Satisfaction, Quality, Health Center.